THU0061 Anemia in patients with rheumatoid arthritis: A cross-sectional study. (23rd January 2014) - Back, J.; Baecklund, E.; Birgegard, G.
Abstract : Background: Anemia has been a common clinical problem in rheumatoid arthritis (RA), in earlier studies reported in 30-60% of RA patients (1). There are few studies of the frequency and type of anemia in RA since the introduction of biologic drugs and more active anti-rheumatic therapy. Objectives: Study the frequency and type of anemia in patients with RA and correlate the findings to clinical characteristics and therapy. Methods: Cross-sectional study. All patients with follow-up for RA at the department of rheumatology, Uppsala University Hospital, Sweden were identified and information about lab variables and clinical data were collected from the medical records. RA was defined according to the 1987 ACR criteria and anemia according to the WHO definition (hemoglobin<120 g/L for women and <130 g/L for men). Results: A total of 1106 patients with RA were identified (mean age 62.6 years, 74.1% women, 75.4% RF-positive). Of the 1106 patients 173 (15.6%) had anemia (17.8% of the men and 14.9% of the women). The anemia was microcytic (mean cell volume <82) in 15.6% of the women and 3.9% of the men. Increased CRP was more common among the anemic patients (71% had CRP>5 mg/L) than in RA patients without anemia (37% with CRP>5mg/L). No significant difference of the frequency of anemia was seen with different drug therapy or among the different biologic drugs (based on low numbers of anemic patients on each biologic drug). Anemia was present in 11.8% of patients treated with biologic drugs, 13.6% of methotrexate-treated patients and in 14.2% of patients treated with NSAIDs on regular basis. Conclusions: The occurrence of anemia in contemporary RA patients seems lower than in earlier studies, but still, in this setting, a substantial part of all RA patients and of patients on biologic therapy (15.6% and 11.8%, respectively) had anemia. Inflammatory activity, as mirrored by elevated CRP, is correlated to the presence of anemia. Increasing knowledge of the mechanisms behind RA-associated anemia now opens for new therapeutic possibilities (2). The benefit and role of specific anemia therapy for these patients remains to be determined. References: Wilson A. Prevalence and outcomes of anemia in rheumatoid arthritis: A systemic review of the literature. Am J Med 2004; 116 (7A): 50S-57S. Andrews NC.Forging a field: the golden age of iron biology.Blood. 2008 Jul 15;112(2):219-30. Disclosure of Interest: None Declared